Farmers’ Perception and Adaptation in Organic Vegetable Production for Sustainable Livelihood in Chiang Mai Province - ณฐิตากานต์ ปินทุกาศ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study aimed to explore farmers’ practice and constraints in organic vegetable farming as well as to identify farmers’ perception and their adaptability in organic vegetable farming, to determine factors influencing farmers’ perception and adaptation in organic vegetable farming and to investigate sustainable development in farmers’ livelihood in the study areas. A total of 108 organic farmers of Chiang Mai Organic Agriculture Cooperative were randomly selected from three districts based on current farming practices experience, in transforming to organic vegetable farming in the tear of 2013. Data were collected using the semi-structured questionnaires and focus group discussion from January to April 2013. The adaptation in organic farming and farm practice were analyzed using three point rating scale method. In order to fulfill the objectives mentioned above, descriptive statistics such as percentage, average, maximum, minimum, standard deviation and multiple regression analysis were used. The findings revealed that farmers in three study areas had experience in organic vegetable production. Organic vegetable farming practice, i.e., land preparation, seed, type of crop, planting method, soil nutrient management, pest management, weed management and harvesting. The disadvantages or constraints inherent in small-farmer adoption of organic agriculture were seen to include: economic, bio-physical and knowledge constraints. The multiple regression analysis results indicated that age, education level, household labor, farm income and extension visit significantly contributed to farmers’ perception on organic vegetable production. Moreover, education level, experience, natural water and farmers’ networks or membership significantly contributed to farmers’ adaptation on organic vegetable production. In conclusion, at present the reduced chemical use in agriculture is an alternative agriculture of farmers. The perception and adaptation in organic vegetable based on five assets such as natural, physical, human, financial and social where is consider to be the key factors for sustaining farmer livelihood. Therefore, the uptake of agricultural extension and policy planner for promoting effective organic agriculture could consider five assets where as the key supporting factors in farmers’ adaptation and perception in organic agriculture which lead to sustainable farmers livelihood.